Data Processing and Modeling on Volcanic and Seismic Areas - Bonforte, Alessandro; Cannavò, Flavio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This special volume aims to collecg new ideas and contributions at the frontier between the fields of data handling, processing and modeling for volcanic and seismic systems. Technological evolution, as well as the increasing availability of new sensors and platforms, and freely available data, pose a new challenge to the scientific community in the development new tools and methods that can integrate and process different information. The recent growth in multi-sensor monitoring networks and satellites, along with the exponential increase in the spatiotemporal data, has revealed an increasingly compelling need to develop data processing, analysis and modeling tools. Data processing, analysis and modeling techniques may allow significant information to be identified and integrated into volcanic/seismological monitoring systems. The newly developed technology is expected to improve operational hazard detection, alerting, and management abilities.